Dampak Persaingan Suku Jawa dan Masyarakat Lokal pada Penguasaan Tempat Strategis di Wisata Kuliner Oepoi - Bernardus Donggo Raga; Yohanes Kornelius Ethelbert; Yasinta Palan Peten; Karolus Tatu Sius; Hendrikus Likusina Kaha (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
Based on data from BPS as of February 2023, from Lifetime Migration (100 Population) in Kupang City, it was recorded that 35.96 were data on residents who migrated into Kupang City, and the net migration figure which reached 33.8 proves that many immigrants from outside Kupang City who want to live and live their lives in Kupang City, including the Javanese who have migrated to Kupang City since the Dutch colonial period in the 19th century. This research aims to examine the theory of gentrification and its relevance in the migration of Javanese to NTT, especially the city. Kupang on the Oepoi Culinary Tour. The method used in this research is a quantitative verification method by testing the truth of theoretical assumptions with data in the field. The results of the research prove that the arrival of Javanese immigrants resulted in changes in terms of demographics, development aesthetics, employment opportunities, social controversy and an increase in property prices. The development of Oepoi Culinary Tourism is correct in arranging the relevant locations to make them look neater, but it must be accompanied by the readiness of the local community in terms of human resources to welcome competition with Javanese people in the culinary world.